P242 Does gastro-oesophageal reflux influence the respiratory tract microbiome in cystic fibrosis patients?. (12th November 2019) - Lord, RW; Einarsson, GG; Lee, AJ; Bianco, B; Whorwell, PJ; Elborn, JS; Tunney, MM; Jones, AM
Abstract : Background: It has been proposed that the increased amounts of gastro-oesophageal reflux seen in cystic fibrosis (CF) patients can lead to reflux aspiration, which in turn may influence the lung microbiome. The aim of this study was to assess microbial community composition of the upper and lower respiratory tracts, and the relationship to intra-oesophageal measures of gastro-oesophageal reflux. Methods: Spontaneous sputum and mouth swill samples were collected from CF subjects (n=17) enrolled in a larger observational study of gastro-oesophageal reflux in CF. All subjects (n=41) had undergone 24 hour combined pH-impedance reflux monitoring. Sampling occurred immediately before reflux monitoring. Genomic DNA was extracted and microbial community profiles determined by sequencing the V4 region of the 16S rRNA marker-gene using the Illumina MiSeq platform. The main measures were alpha-diversity (taxonomic richness, Shannon-Wiener diversity, evenness and dominance) and beta-diversity (PERMANOVA and mean distance to group centroid) . Reflux measures of interest were selected (total events, proximal events and acid exposure), and based on these the subjects were divided into tertiles for analyses of relationships to microbiome measures. Results: For the sputum samples there was no difference in alpha-diversity for any tested reflux measure. However, for oral rinse samples there were significant differences noted for total reflux for alpha-diversity (richness (p=0.016); Shannon-Wiener diversity (p=0.007); and dominance (p=0.007)). Proximal reflux showed some trend toward significance (Shannon-Wiener diversity (p=0.093); evenness (p=0.113); and dominance (p=0.073)). No significant difference or trend was noted for acid exposure. There were no differences observed in beta diversity for any reflux measure for mouth rinses or sputum samples (p>0.05). Conclusions: Our data suggests that intra-oesophageal measures of reflux do not affect the lower respiratory tract microbiome, but may influence the upper respiratory tract microbiome. This may relate to the requirement for reflux to overcome upper airway defences in order to reach the lower respiratory tract, but not the upper respiratory tract. We intend to further investigate this finding using a larger cohort of mouth swill samples (n=24), as well as aiming to repeat these analyses for upper and lower respiratory tract samples following the development of a biomarker of extra-oesophageal reflux.